The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fnins.2017.00105
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Resveratrol on Glucose Control, Hippocampal Structure and Connectivity, and Memory Performance in Patients with Mild Cognitive Impairment

Abstract: In healthy older adults, resveratrol supplementation has been shown to improve long-term glucose control, resting-state functional connectivity (RSFC) of the hippocampus, and memory function. Here, we aimed to investigate if these beneficial effects extend to individuals at high-risk for dementia, i.e., patients with mild cognitive impairment (MCI). In a randomized, double-blind interventional study, 40 well-characterized patients with MCI (21 females; 50–80 years) completed 26 weeks of resveratrol (200 mg/d; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 56 publications
1
83
1
Order By: Relevance
“…Most of the polyphenols constituting our pattern have documented clinical effects in cognitive aging and AD. For example, in moderately-sized trials (N<150), moderate to high doses of resveratrol (ie, 200-2000 mg/day) increased hippocampal connectivity and memory in older adults, 30,31 and decreased plasma and cerebrospinal fluid amyloid-β levels in AD patients. 32 Moreover, a few small trials demonstrated efficacy of flavanols in increasing hippocampal vascular plasticity, 33 and of both citrus flavanones and soy isoflavonoids in improving cognition in older persons.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the polyphenols constituting our pattern have documented clinical effects in cognitive aging and AD. For example, in moderately-sized trials (N<150), moderate to high doses of resveratrol (ie, 200-2000 mg/day) increased hippocampal connectivity and memory in older adults, 30,31 and decreased plasma and cerebrospinal fluid amyloid-β levels in AD patients. 32 Moreover, a few small trials demonstrated efficacy of flavanols in increasing hippocampal vascular plasticity, 33 and of both citrus flavanones and soy isoflavonoids in improving cognition in older persons.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hippocampus volume, microstructure, and resting‐state functional connectivity were analyzed using cerebral magnetic resonance imaging ( n = 14 vs. 16), and neuropsychological tests assessing learning and memory were performed . Compared with controls, the group receiving resveratrol supplementation showed a decrease in glycated hemoglobin A1c concentration, a statistically significant increase in resting‐state functional connectivity between right anterior hippocampus and right angular cortex, and a moderate preservation of left anterior hippocampus volume (Cohen's d = 0.68) . This proof‐of‐concept study indicates that resveratrol supplementation may reduce glycated hemoglobin A1c, preserve hippocampus volume, and improve resting‐state functional connectivity of the hippocampus in individuals at risk for dementia.…”
Section: Intervention Trials Of Resveratrol In Humansmentioning
confidence: 75%
“…In healthy elderly adults, resveratrol supplementation (200 mg daily for 26 weeks) has been shown to enhance verbal episodic memory performance, long‐term glucose control, and resting‐state functional connectivity between the hippocampus and neocortical brain areas . A further study examined whether these favorable effects could also be observed in patients with mild cognitive impairment . In a randomized, double‐blind interventional study, 40 mildly cognitively impaired individuals (aged 50–80 years, 21 females, 19 males) were administered either resveratrol (200 mg/d; n = 18) or placebo (1,015 mg/d olive oil; n = 22) for 26 weeks.…”
Section: Intervention Trials Of Resveratrol In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, conflicting results [57, 58] and the lack of confirmation of several mechanisms involved in its activity in ‘preclinical’ models [52] preclude its current pharmacological use in patients with or at high risk of diabetes, or at high risk for development of cognitive impairment. However, recent clinical trials support the notion that resveratrol is capable of increasing cerebral blood flow during task performance [59, 49, 60] and enhancing oxygen extraction [49], reducing glycated hemoglobin A1c, preserving hippocampus volume, and improving hippocampus resting state functional connectivity in at-risk patients for dementia [61]. A randomized, double-blind clinical trial phase 1 (NCT02502253) will evaluate the effects of a Bioactive Dietary Polyphenol Preparation (BDPP), a combination of two nutraceutical preparations (grape seed polyphenolic extract, and resveratrol) in mood and cognition of patients with MCI and prediabetes or type 2 diabetes.…”
Section: Emerging Therapeutic Approachesmentioning
confidence: 99%